INFLUENCE OF IDEALIZED BEHAVIOUR ON THE IMPLEMENTATION OF CDF CONSTRUCTION PROJECTS IN PUBLIC SECONDARY SCHOOLS IN KISUMU COUNTY, KENYA - Janet, Wagude; Rambo, Charles; Ndiritu, Anne; Onyango, Maria (European Scientific Journal, ESJ, 2015)
Idealized behavior is an aspect of transformational leadership which defines the need for change, developing a vision for the future, and mobilizing followers for commitment to achieve results beyond what is expected. This study explored the Influence of Idealized behavior on projects implementation. A case study is that of constituency Development Fund construction projects in public secondary schools in Kisumu County, Kenya. The objective of this study is to examine how idealized behavior influences the implementation of CDF construction projects. The study used Expost facto design and it was anchored on three theories: the transformational leadership theory, contingency theory, and systems theory. Hypotheses was formulated and subsequently tested in the study in order to establish the influence of conflict resolution thereof. In hypothesis H1, (H0: The strength of the relationship between idealized behavior and the implementation of CDF projects does not depend on conflict resolution), it was concluded that the strength of the relationship between idealized behavior and the implementation of CDF projects depends on conflict resolution (P=0.013˂P=0.05).